Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/rs11212530
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Accuracy of Landslide Detection in “Off-site” Area by Machine Learning Model Portability Comparison: A Case Study of Jiuzhaigou Earthquake, China

Abstract: The rising machine learning (ML) models have become the preferred way for landslide detection based on remote sensing images, but the performance of these models in a sample-free area are rarely concerned in many studies. In this study, we used a cross-validation method (training model in one area and validation in another) to compare the model portability of trained ML models applied in an “off-site” area, as a consideration of the landslide detection ability of these models in sample-free areas. We integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Deep learning techniques do not require hand-crafted features as they perform automatic feature engineering directly from satellite imagery. Hu et al [42] used landslide images from multiple seasons from LandSat satellite and digital elevation model (DEM) data to extract landslides using three ML models. Prakash et al [11] used Sentinel-2 images, DEM data from light detection and ranging (Lidar), and a derived normalized difference vegetation index (NDVI) layer to map landslides using a modified U-Net model [48], [49].…”
Section: A Landslide Mappingmentioning
confidence: 99%
“…Deep learning techniques do not require hand-crafted features as they perform automatic feature engineering directly from satellite imagery. Hu et al [42] used landslide images from multiple seasons from LandSat satellite and digital elevation model (DEM) data to extract landslides using three ML models. Prakash et al [11] used Sentinel-2 images, DEM data from light detection and ranging (Lidar), and a derived normalized difference vegetation index (NDVI) layer to map landslides using a modified U-Net model [48], [49].…”
Section: A Landslide Mappingmentioning
confidence: 99%
“…Deep learning, a branch of ML, has also been used for landslide mapping [20], [29]- [34]. Deep learning techniques are more efficient in terms of automatic feature engineering directly from satellite imagery.…”
Section: B Deep Learning Approaches and Limitations Of Homogeneous Training Datamentioning
confidence: 99%
“…Deep learning techniques are more efficient in terms of automatic feature engineering directly from satellite imagery. [29] used landslide images from multiple seasons from LandSat satellite and DEM data to extract landslides using three ML models. [32] used Sentinel-2 images, DEM data from Lidar, and a derived NDVI layer to map landslides using a modified U-Net model [7].…”
Section: B Deep Learning Approaches and Limitations Of Homogeneous Training Datamentioning
confidence: 99%
“…Commonly used methods include support vector machines (SVM), decision trees (DTs), random forest (RF), and artificial neural networks (ANN) [20]. Among them, [21,22] have demonstrated that RF exhibited stable portability on new data compared to SVM and ANN. Piralilou et al [23] proposed a landslide detection method connecting the result of OOA with logistic regression, multilayer perceptron, and RF by the Dempster-Shafer theory.…”
Section: Introductionmentioning
confidence: 99%